Pengaruh Penggunaan Media ICT dalam Pembelajaran Inkuiri pada Topik Bioteknologi Terhadap Kemampuan Berpikir Tingkat Tinggi Siswa MAN 3 Medan - Satriawati Satriawati; Ely Djulia; Fauziyah Harahap (Jurnal Pendidikan Biologi, 2016)
This study aims to investigate the effect of implementing the ICT media in learning inquiry about biotechnology into: Student’s higher order thingking skill; of students in class XII IPA at MAN 3 Medan.The study use quasy eksperimentwith sample as much as 3 class wich certained cluster random samplingof class XII IPA1learning process use learning video media, class XII IPA2learning process use animation media and class XII IPA3with use charta (control). Research instrumentuse higher order thingking skill test of students with use multiple choice and essay test. Analysis techniq using analysis covarians with usingby program SPSS 21.0.Study result and analysis show there are: Effect wich very significant (F=11,272; P=0,000) with using learning video media, animation, and charta of inquiry learning of the biotechnology topic to higher order thingking skill. Higher order thingking skillthat were taught by learning video (75,82±7,847) different significant with animasi (70,74±7,549) (P=0,010) and different significant with charta (65,38±7,162) (P=0,000).The result of this study is expectedfrom the teachersto applymedia of learning video and animation with inquiry of the biotechnology topicin order to increase higher order thingking skill of students in class XII IPA at MAN 3 Medan.